Mali: OMA - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
OMA (Agricultural Market Watch) officials gather information on the prices of millet, rice and livestock on 58 local markets, and email the results to regional offices.